A story environment for learning object annotation and collection : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Computer Science at Massey University, Palmerston North, New Zealand - Chen, Tianjiao (Massey University, 2005)
With the increase in computer power, network bandwidth and availability, e-learning is used more and more widely. In practice e-learning can be applied in a variety of ways, such as providing electronic resources to support teaching and learning, developing computer based tutoring programs or building computer supported collaborative learning environments. Nowadays e-learning becomes significantly important because it can improve the quality of learning through using interactive computers, online communications and information systems in ways that other teaching methods cannot achieve. The important advantage of e-learning is that it offers learners a large amount of sharable and reusable learning resources. The current approaches such as Internet search and learning object repository does not effectively help users to search for appropriate learning objects. The original story concept introduces a new semantic layer between collections of learning objects and learning material. The basic idea of the story concept is to add an interpretative, semantically rich layer, informally called 'Story' between learning objects and learning material that links learning objects according to specific themes and subjects (Heinrich & Andres, 2003a). One motivation behind this approach is to put a more focused, semantic layer on top of untargeted metadata that are commonly used to describe a single learning object. Speaking from an e-learning context the stories build on learning objects and become information resources for learning material. The overall aim of this project was to design and build a story environment to realize the above story concept. The development of the story environment includes story metadata, story environment components, the story browsing and authoring processes, and tools involved in story browsing and authoring. The story concept suggests different types of metadata should be used in a story. This project developed those different metadata specifications to support story environment. Two prototypes of tools have been designed and implemented in this project to allow users to evaluate the story concept and story environment. The story browser helps story readers to read the story narrative and look at a story from different perspectives. The story authoring tool is used by the story authors to author a story. The future work of this project has been identified in the area of adding features of current tools, user testing and further implementation of the story environment.
Keywords: Interactive multimedia; Multimedia systems; Instructional systems -- Design; Computer-assisted instruction